Analysis of the Role of Sustainable Entrepreneurship Education to Increase Interest in Entrepreneurship in the Digital Era Through Literature Review Analysis - Mufida, Amatulloh; Utomo, Eko Budi; Sukamto, Dinda Dwi Lukita; Benita, Almas Zerlina; Wulandari, Siti Sri; Susanti, Susanti (Jurnal Pendidikan Edutama, 2024)
This research aims to describe the results of research regarding the analysis of the role of sustainable entrepreneurship education in increasing interest in entrepreneurship in the digital era. This research method is a qualitative study with a Systematic Literature Review (SLR). In this research, SLR is important to reduce sampling by providing differences/relationships between one piece of literature and another. The research sample is articles indexed by Scopus, Google Scholar, and Sinta. The keywords used in searches using Google were "sustainable AND entrepreneurship AND education: AND entrepreneurial AND interest" from 2015 - 2024. A total of 56 articles were gotten through look on Scopus, Google Researcher, and Sinta. The research results show that sustainable entrepreneurship education plays an important role in building and developing entrepreneurship. The main role of sustainable entrepreneurship education includes education about, through, and for companies. The strategy to foster an entrepreneurial spirit in schools involves preparing educated staff and educators who have an entrepreneurial spirit. Educational institutions are playing a greater role in fostering the entrepreneurial spirit.